STRATEGI FILANTROPI ISLAM BERBASIS MEDIA DIGITAL - Kharima, Nadya; Muslimah, Fauziah; Anjani, Aninda Dwi (Social Welfare Study Program, 2021)
Abstract. The phenomenon of digital media utilisation is currently in turmoil, in addition to the increasing need due to the coronavirus outbreak (COVID-19) which forces us to always be connected. The use of digital media is a form of adaptation in terms of communication during a pandemic. One of the Islamic philanthropies that uses digital media is the Wisata Panti (Orphanage Tourism) Community. Founded in 2015, this community maximizing the use of various media platforms, starting from the website, Instagram, YouTube and Facebook. With the presence of this orphanage tourism community, it can refer for researchers to see how Islamic philanthropic strategies based on digital media. This research uses a qualitative approach, with a descriptive case study strategy. This study aims at understanding comprehensively and deeply how the digital media-based Islamic philanthropic strategy is carried out by the Wisata Panti community. This research draws several conclusions including; Firstly, in the digital era, social media has become a new platform for promotion in the form of community branding. Secondly, social media can be a new platform for raising funds or online donations that finance social activities in WP. Thirdly, being active on social media is done with a special strategy of good content management. Fourthly, the success of community branding on social media has allowed the WP Community to legally turn into a Foundation. Fifthly, some shortcomings are not so significant in terms of the number of followers, likes, and comments. However, from the start, it was not the focus of WP's social media goals, which only wanted to share promotional content for social activities and fundraising. Abstrak. Fenomena penggunaan media digital saat ini tengah bergejolak. Di samping karena kebutuhan yang makin tinggi akibat wabah virus corona (COVID-19) yang memaksa kita untuk selalu terhubung, penggunaan media digital sebagai salah satu bentuk adaptasi dalam hal komunikasi di masa pandemi. Salah satu filantropi Islam yang menggunakan media digital adalah Komunitas Wisata Panti (WP). Sebuah komunitas yang berdiri pada tahun 2015 dengan berbagai platform media yang digunakan, mulai dari website, Instagram, YouTube dan Facebook. Dengan kehadiran komunitas wisata panti ini dapat membuat referensi bagi peneliti untuk melihat bagaimana strategi filantropi islam berbasis media digital. Penelitian ini menggunakan pendekatan kualitatif, dengan strategi studi kasus secara deskriptif. Hal tersebut dikarenakan penelitian ini memiliki tujuan untuk menjawab pertanyaan rumusan masalah secara komprehensif dan mendalam mengenai bagaimana strategi filantropi Islam berbasis media digital yang dilakukan komunitas Wisata Panti. Selanjutnya, berdasarkan latar belakang dan metode tersebut, hasil penelitian ini adalah; pertama, di era digital media sosial menjadi sebuah wadah baru untuk melakukan promosi berupa community branding. Kedua, media sosial bisa menjadi wadah baru untuk galang dana atau donasi online yang membiayai kegiatan sosial di WP. Ketiga, aktif di media sosial tersebut dilakukan dengan strategi khusus manajemen konten yang baik. Keempat, kesuksesan community branding di media sosial membuat komunitas WP bisa beralih menjadi Yayasan secara legal. Kelima, ada kekurangan yang memang dari segi jumlah followers, like, dan komen tidak begitu signifikan pertambahannya. Berdasarkan hasil wawancara, fokus tujuan media sosial WP adalah untuk membagikan konten promosi kegiatan sosial dan galang dana.